“Became Superfluous in Crimea”: Ups and Downs of Fate of Professor P. A. Dvoichenko (Correspondence with V. I. Vernadsky) - A. A. Nepomnyashchy (Научный диалог)
The question of the scientific life of the Crimean University (Pedagogical Institute) named after M. V. Frunze in the 20s — early 30s of the XX century through the correspondence of Professor P. A. Dvoychenko and Academician V. I. Vernadsky. It is shown that after leaving Simferopol in February 1921, Academician V. I. Vernadsky, who was involved in the birth of natural science research at the Tauride University, was keenly interested not only in the progress of these studies, but also in the fate of the scientists who made up his entourage in Simferopol. It is argued that Vernadsky’s epistolary communication with Professor Petr Abramovich Dvoichenko makes it possible to identify scientific developments initiated in the Crimea by Vernadsky, on which Crimean scientists continued to work. It is noted that the study of correspondence made it possible to reveal previously unknown pages of the biography of P. A. Dvoychenko. The novelty of the research is seen in the involvement of the epistolary heritage for the reconstruction of the historical everyday life of the scientists Vernadsky, Dvoichenko and their entourage. It is emphasized that the correspondence of scientists allows us to study the tension among the researchers of the Crimea, to see the features of scientific contacts along the line “province — center”. The author dwells on individual plots of interpersonal interaction in the teaching environment of the university.